Ethyl gallate isolated from phenol-enriched fraction of Caesalpinia mimosoides Lam. Promotes cutaneous wound healing: a scientific validation through bioassay-guided fractionation - Bhat, Pradeep; Patil, Vishal S.; Anand, Ashish; Bijjaragi, Subhas; Hegde, Ganesh R.; Hegde, Harsha V.; Roy, Subarna (Frontiers in Pharmacology, 2023)
The tender shoots of Caesalpinia mimosoides Lam. are having ethnomedicinal claims among the traditional healers of Uttara Kannada district, Karnataka (India) for the treatment of wounds. The current study was aimed at exploring phenol enriched fraction (PEF) of crude ethanol extract of tender shoots to isolate and characterize the most active bio-constituent through bioassay-guided fractionation procedure. The successive fractionation and sub-fractionation of PEF, followed by in vitro scratch wound, antimicrobial, and antioxidant activities yielded a highly active natural antioxidant compound ethyl gallate (EG). In vitro wound healing potentiality of EG was evidenced by significantly higher percentage of cell migration in L929 fibroblast cells (97.98±0.46% at 3.81 µg/ml concentration) compared to a positive control group (98.44±0.36%) at 48th hour of incubation. A significantly higher rate of wound contraction (98.72±0.41%), an elevated tensile strength of incised wound (1154.60±1.42 g/mm2), and increased quantity of connective tissue elements were observed in the granulation tissues of 1% EG ointment treated animal group on 15th post-wounding day. The accelerated wound healing activity of 1% EG was also exhibited by histopathological examinations through Hematoxylin & Eosin, Masson’s trichome and Toluidine blue stained sections. Significant up-regulation of enzymatic and non-enzymatic antioxidant contents (reduced glutathione, superoxide dismutase, and catalase) and down-regulation of oxidative stress marker (lipid peroxidation) clearly indicates the effective granular antioxidant activity of 1% EG in preventing oxidative damage to the skin tissues. Further, in vitro antimicrobial and antioxidant activities of EG supports the positive correlation with its enhanced wound-healing activity. Moreover, molecular docking and dynamics for 100 ns revealed the stable binding of EG with cyclooxygenase-2 (-6.2 kcal/mol) and matrix metalloproteinase-9 (-4.6 kcal/mol) and unstable binding with tumor necrosis factor-α (-7.2 kcal/mol) suggesting the potential applicability of EG in inflammation and wound treatment.